Non‐Pincer‐Type Mononuclear Scandium Alkylidene Complexes: Synthesis, Bonding, and Reactivity. Issue 4 (16th December 2015) - Wang, Chen; Zhou, Jiliang; Zhao, Xuefei; Maron, Laurent; Leng, Xuebing; Chen, Yaofeng
Abstract: The first non‐pincer‐type mononuclear scandium alkylidene complexes were synthesized and structurally characterized. These complexes exhibited short Sc−C bond lengths and even one of the shortest reported to date (2.1134(18) Å). The multiple character of the Sc−C bond was highlighted by a DFT calculation. This was confirmed by experimental reactivity study where the complex underwent [2+1] cycloaddition with elemental selenium and [2+2] cycloaddition with imine. DFT calculation also revealed a strong nucleophilic behavior of the alkylidene complex that was experimentally demonstrated by the C−H bond activation of phenylacetylene. Abstract : The first non‐pincer‐type mononuclear scandium alkylidene complexes were synthesized and structurally characterized. These complexes exhibited very short Sc−C bond lengths. The multiple bond character as well as the strong nucleophilic behavior of the alkylidene group was underlined by NBO and NPA calculations but also demonstrated by experimental reactivity study.